Assessment of Microplastics in the Surface Water of Sitio Pulo, Navotas, Metro Manila - Mark Lester C. Galicia; Carl Luis P. Flestado; Jeff Ryan S. Magalong; Ronald Benz L. Rivera; Kim M. Villacorte; William Peter G. Sarmiento; Chester C. Deocaris (Applied Environmental Research, 2023)
Microplastics are synthetic polymer particles with a length of 5 mm or less with no well-defined lower boundary. These debris particles are known to affect marine and aquatic organisms which poses a threat to biodiversity and marine resources. In this study, the isolated microplastic from the coastal and lagoon surface waters of Sitio Pulo is described. Sitio Pulo is a barrier island mangrove sanctuary located at Brgy. Tanza I, Navotas City surrounded by Manila Bay. The samples collected last July 4 and 25, 2019, were isolated, profiled, and analyzed. A total of four hundred forty-nine (449) microplastic fragments were isolated from the surface water samples with a median length of 1.096 (IQR 0.809–1.578) mm. The isolated microplastics exhibit roundness, whiteness, and yellowing indicating signs of mechanical, chemical and photodegradation. It is also noted the putative effects of the weather disturbances in accelerating the discharge of nascent microplastics in Manila Bay. The isolated microplastic composition includes the commodity polymers polyethylene (PE) and polypropylene (PP). The presence of microplastics in the surface waters of Sitio Pulo reflects the worsening plastic pollution problem in Metro Manila.